1983
DOI: 10.2136/sssaj1983.03615995004700050047x
|View full text |Cite
|
Sign up to set email alerts
|

Atterberg Limits as Indices of External Surface Areas of Soils

Abstract: Surface area measurements on soils are usually laborious and require expensive equipment. The relationship between Atterberg limits (plastic and liquid) and surface area is investigated with a view to being able to estimate the latter from the former. The results show that there is a very strong relationship (r2 > 0.9) which permits surface area to be estimated rapidly and cheaply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As shown above with particle density, it is well known that clay content, SOM content, and clay mineralogy also strongly infl uence the soil consistency limits, largely by way of their infl uence on the specifi c surface (Hammel et al, 1983;Dolinar et al, 2007). Th ese inter-relationships are clearly shown in Table 2 by the strong correlations involving the consistency limits and both clay and SOM contents, with the exception of w P and clay content.…”
Section: Soil Mechanical Propertiesmentioning
confidence: 81%
“…As shown above with particle density, it is well known that clay content, SOM content, and clay mineralogy also strongly infl uence the soil consistency limits, largely by way of their infl uence on the specifi c surface (Hammel et al, 1983;Dolinar et al, 2007). Th ese inter-relationships are clearly shown in Table 2 by the strong correlations involving the consistency limits and both clay and SOM contents, with the exception of w P and clay content.…”
Section: Soil Mechanical Propertiesmentioning
confidence: 81%
“…They stated that the external surface of particles, quality of pore water and the valence of exchangeable cation are important factors that influence on the soil plasticity. Hammel et al (1983) presented a relationship between the external surface and Atterberg limits. It can be said that the type of the soil minerals, pore fluid salt concentration and cation valance affect the surface area of soil and thickness of DDL.…”
Section: Discussionmentioning
confidence: 99%
“…The physical properties of soil are not isolated and often associated with each other. Many researchers have found that the SSA of clay is closely related to the LL, e.g., finding a linear relationship between the SSA and LL [23,24,[37][38][39][40][41][42] or that the reciprocal of the SSA has a linear relationship with the reciprocal of the LL [21,32,43], and a good power function relationship between the SSA and LL [38,[44][45][46][47]].…”
Section: Definition and Application Of Specific Surface Area (Ssa) Inmentioning
confidence: 99%